Preparation and characterisation of biodegradable pollen–chitosan microcapsules and its application in heavy metal removal - Sargin, Idris; Kaya, Murat; Arslan, Gulsin; Baran, Talat; Ceter, Talip (Elsevier BV, 2015)
Biosorbents have been widely used in heavy metal removal. New resources should be exploited to develop more efficient biosorbents. This study reports the preparation of three novel chitosan microcapsules from pollens of three common, wind-pollinated plants (Acer negundo, Cupressus sempervirens and Populus nigra). The microcapsules were characterized (Fourier transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy and elemental analysis) and used in removal of heavy metal ions: Cd(II), Cr(III), Cu(II), Ni(II) and Zn(II). Their sorption capacities were compared to those of cross-linked chitosan beads without pollen grains. C. sempervirens-chitosan microcapsules exhibited better performance (Cd(II): 65.98; Cu(II): 67.10 and Zn(II): 49.55 mg g(-1)) than the other microcapsules and the cross-linked beads. A. negundo-chitosan microcapsules were more efficient in Cr(III) (70.40 mg g(-1)) removal. P. nigra-chitosan microcapsules were found to be less efficient. Chitosan-pollen microcapsules (except P. nigra-chitosan microcapsules) can be used in heavy metal removal.
Keywords: Chitosan; Time Factors; Surface Properties; Biosorbent; Capsules; Hydrogen-Ion Concentration; Models, Theoretical; Plants; Heavy Metal; Heavy metal; Microcapsule; Biodegradation, Environmental; Metals, Heavy; Spectroscopy, Fourier Transform Infrared; Thermogravimetry; Pollen; Thermodynamics; Adsorption; 2. Zero hunger